IMPLEMENTASI ALGORITMA PATHFINDING DAN DECISION TREE DALAM PEMBUATAN VIDEO GAME BERGENRE THIRD PERSON SHOOTER - Sugianto, Bambang; Utama, Gunawan Pria (Universitas Budi Luhur, 2021)
Video Games are games that use electronic device technology that provides images as a medium that is related to the user and the user can control the objects that are in the picture with a controller (Input Device). During the times, Video Games have other output media (output) such as sound and vibration. Budi Luhur University has a community that prioritizes Creative Boxes, which is a video game developer community at Budi Luhur University. Creative Box Community has made several games for the Android and PC platforms. However, this community has never implemented a special Artificial Intelligence (AI) technique in the game title created by the Creative Box community. Therefore, the main objective of this Final Project is to create AI content in the Third Person Shooter (TPS) genre as the main opponent, because the TPS genre is used as the main opponent as the main source. For this reason, the Pathfinding Method is needed to determine the direction of the road and the Decision Tree as the determinant of the action (behavior) of the main opponent. Pathfinding method uses Algorithm A *, how to take by taking the distance between each node and destination. The Decision Tree method is a hierarchical tree that is implemented using Nested if-else, each condition will be made and a decision is made based on the condition.